Management of Mechanical Problems of Totally Implantable Venous Catheters - Kara, Halil; Arikan, Akif Enes; Dulgeroglu, Onur; Uras, Cihan (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Although the most common complications of totally implantable venous catheters(TIVC) are infection and thrombosis, mechanical complications can also affect the treatment and cause catheter removal. This study aimed to investigate mechanical complications of TIVC and prevention methods. Methods: Data of 983 procedures in 961patients who underwent TIVC implantation between 2010 and 2019 in AcibademMaslak, Bakirkoy, and Atakent Hospitals were retrospectively analyzed for mechanical complications. Results: Mechanical complications were encountered in 33(3.3\%) cases: 12(1.2\%) were detachment of TIVC, 8(0.8\%) occlusions, 5(0.5\%) pneumothorax, 1(0.1\%) hemothorax, 1(0.1\%) malposition, 1(0.1\%) extravasation, 2(0.2\%) TIVC rotation, 3(0.3\%) skin necrosis and extrusions. Conclusion: The catheter tip should be placed in distal superior vena cava, reservoir pocket must be sufficient in size, reservoir should be fixed to pectoral muscle or fascia at least two points with nonabsorbable sutures. Subcutaneous fatty tissue resection from reservoir pocket should be performed in obese patients. The nature of the withdrawn blood form Seldinger needle should be checked visually whether venous or not. Risk of pneumothorax and detachment can be reduced by inserting the catheter from 1/3 outer part of the clavicle during percutaneous technique. While complication rate can be reduced by peroperative fluoroscopy use, control X-ray should be taken in symptomatic patients, not routinely. Malposition can be seen in the peroperative period and can usually be corrected by good manipulation. Percutaneous transcatheter retrieval in addition to surgery is the gold standard treatment for detachment of TIVC. The most important factors in preventing complications are surgical experience and good care.
Keywords: Totally implantable venous catheter; complication; detachment; malfunction; malposition